- #1

- 48

- 0

## Homework Statement

i'm viewing an example written in class. it looks like this:

f(x

_{1}, x

_{2}, x

_{3}, x

_{4}) = [(not x

_{1}) * x

_{2}* x

_{4}] ∨ [x

_{2}* x

_{3}* x

_{4}]

what should be function after applying absorption law?

## Homework Equations

i know how another option called "gluing" works:

[x

_{1}* x

_{2}* x

_{3}] ∨ [(not x

_{1}) * x

_{2}* x

_{3}] = x

_{2}* x

_{3}

## The Attempt at a Solution

our teacher wrote f(x

_{1}, x

_{2}, x

_{3}, x

_{4}) = x

_{2}* x

_{3}* x

_{4}but i'm having a hard time to understand why